Do morphological adaptations for gliding in frogs influence clinging and jumping?. (4th September 2019) - McKnight, D. T.; Nordine, J.; Jerrett, B.; Murray, M.; Murray, P.; Moss, R.; Northey, M.; Simard, N.; Alford, R. A.; Schwarzkopf, L.
Abstract: The ability to glide has evolved in multiple taxa and is usually associated with highly specialized morphological adaptations. Traits that evolve for one reason, can, however, influence other traits and abilities. In this study, we examined the influence of adaptations for gliding on the jumping and clinging abilities of frogs by comparing specialized flying frogs ( Rhacophorus ) and unspecialized non‐flying frogs ( Polypedates ) from the family Rhacophoridae. Flying frogs had more webbing, longer legs, and greater clinging abilities than non‐flying frogs. Clinging abilities, jumping distance, and gliding distance all correlated positively with body size for both flying and non‐flying frogs. We did not, however, find any significant differences between the two groups in horizontal jumping distance or glide distance from a low starting point of 1.56 m. The morphological adaptations that evolved for gliding have not significantly influenced the flying frogs' short‐distance jumping abilities, but may have influenced their clinging abilities. Alternatively, there may have been direct selection for clinging ability because of flying frogs' increased need, compared with other frogs, to land on vertical surfaces without slipping off. Abstract : The ability to glide has evolved in multiple taxa and is associated with specialized morphological adaptations. In this study, we examined the influence of adaptations for gliding on the jumping and clinging abilities of frogs, and we found that flying frogs had greater clinging ability than non‐flying frogs. There may have been direct selection for clinging ability because of flying frog's increased need to land on vertical surfaces without slipping.